Characterization of Staphylococcus aureus by pulsed field gel electrophoresis - CHOUGULE, M N; GANDGE, R S; BANNALIKAR, A S; MAJEE, S B (The Indian Journal of Animal Sciences, 2015)
Staphylococcus aureus is reported as principal cause accounting for more than 19 to 40% of the cases of bovine mastitis. The pulsed field gel electrophoresis (PFGE) which is currently considered as the gold standard method was used in the present study for characterization of S. aureus. S. aureus isolates (29) recovered from bovine mastitis milk samples were subjected to the PFGE. Out of 29 isolates, 22 could be digested by SmaI enzyme and yielded dendrogram showing 2 major clusters with 8 pulsotypes (A to H) having > 60% similarity coefficient. The pulsotype A, C, D and F were constituted of isolates recovered from both cows and buffaloes, whereas pulsotype B and H were from buffaloes only and pulsotype E and G were from cattle origin. The pulsotype A isolates were coagulase negative while all the isolates of pulsotype F and H were coagulase positive; and pulsotype B, C, D, E and G were having both coagulase positive and negative isolates. No correlation between geographical area and other virulence factors was observed, since isolates belonged to diverse origin of locations from 2 different districts of western Maharashtra. Thus, PFGE proved to be a good tool for genetic discrimination of S. aureus strains in molecular epidemiology.